Workplace Exposures and Cognitive Function During Adulthood: Evidence From National Survey of Midlife Development and the O*NET. Issue 6 (June 2016) - Grzywacz, Joseph G.; Segel-Karpas, Dikla; Lachman, Margie E.
Abstract : Objective: Expand understanding of the role of selected workplace exposures (ie, occupational complexity, conflict in the workplace, pace of work, and physical hazards) in adults' cognitive function. Methods: Cross-sectional data ( n  = 1991) from the second wave of the Midlife in the United States (MIDUS) study; restricted to participants who completed telephone-based cognitive assessments of episodic memory, executive functioning, and self-perceived memory. Occupational exposure data were harvested from the O * NET Release 6.0. Results: Greater complexity was associated with better self-perceived memory among women and men, and better episodic memory and executive functioning among women. Greater physical hazards were independently associated with poorer episodic memory and executive functioning. Conclusions: Objective assessments of physical and psychosocial exposures in the workplace are independently associated with cognitive outcomes in adulthood, with psychosocial exposures being particularly pronounced among women.